Safety assessment of the process Fucine Film, based on the Reifenhäuser technology, used to recycle post‐consumer PET into food contact materials - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Andrew Chesson; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; et al. (EFSA Journal, 2024)
Abstract The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process Fucine Film (EU register number RECYC322), which uses the Reifenhäuser technology. The input material consists of hot caustic washed and dried poly(ethylene terephthalate) (PET) flakes mainly originating from collected post‐consumer PET containers, including no more than 5% PET from non‐food consumer applications. The flakes are extruded under vacuum into sheets. The recycled sheets are intended to be used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs, excluded drinking water and beverages, for long‐term storage at room temperature, with or without hotfill. Based on the limited data available, the Panel concluded that the information submitted to EFSA was inadequate to demonstrate that the recycling process Fucine Film is able to reduce potential unknown contamination of the input PET flakes to a concentration that does not pose a risk to human health.